I figure 2+2=5 heres how... If a=4 b=5 c=1 then c=b-a/(b-a) then c(b-a) = (b-a)^2 (^2 means squared) then cb-ca=b^2 -2ab=a^2/-a^2 then cb-ca-a^2=b^2-2ab/ab then ab+cb-ca-a^2=b^2-ab/-cb then a(b-c-a)=b(b-c-a) then a=b and a=4 and b=5 and 2+2=4 and 4=5 then... 2+2=5 right? Where's my tylenol.

If you are using Chicken Math........ 2 + 2 = 2 2 Bantams = 1 Large Fowl so if you have 4 Bantams that = 2 Large Fowl See 2 + 2 = 2

Take this to your math teacher.....for a laugh or two. I used to do things like this to my Algebra teacher.....the put me in AP calculus....I don't think I won that one....

your second step is incorrect due to parentheses placement. I don't feel like typing it out, but it is. So the whole thing doesn't make sense.

Here's another one... I can prove that 2=1 x=y x-y=0 2x-2y=0 2x-2y=x-y 2(x-y) = (x-y) 2(x-y) = (x-y)/x-y therefore 2=1 one more... a=1 b=1 aa=ab a^2 = ab a^2-b^2=ab-b^2 (a+b)(a-b) = b(a-b) a+b=b that means 2=1 My teachers HATED ME!